A randomized controlled trial of oxygen therapy in acute myocardial infarction Air Verses Oxygen in myocarDial infarction study (AVOID Study) - Stub, D.; Smith, K.; Bernard, S.; Bray, Janet; Stephenson, M.; Cameron, P.; Meredith, I.; Kaye, D. (2012)
Background: The role of routine supplemental oxygen for patients with uncomplicated acute myocardial infarction (AMI) has recently been questioned. There is conflicting data on the possible effects of hyperoxia on ischemic myocardium. The few clinical trials examining the role of oxygen in AMI were performed prior to the modern approach of emergent reperfusion and advanced medical management. Methods: Air Verses Oxygen In myocarDial infarction study (AVOID Study) is a prospective, multi-centre, randomized, controlled trial conducted by Ambulance Victoria and participating metropolitan Melbourne hospitals with primary percutaneous coronary intervention capabilities. The purpose of the study is to determine whether withholding routine supplemental oxygen therapy in patients with acute ST-elevation myocardial infarction but without hypoxia prior to reperfusion decreases myocardial infarct size. AVOID will enroll 490 patients, >18 years of age with acute ST-elevation myocardial infarction of less than 12 hours duration. Conclusions: There is an urgent need for clinical trials examining the role of oxygen in AMI. AVOID will seek to clarify this important issue. Results from this study may have widespread implications on the treatment of AMI and the use of oxygen in both the pre-hospital and hospital settings.